Contenidos deportivos en diarios impresos El Extra y El Comercio ante la participación de Ecuador Eliminatorias Mundial de Futbol Qatar 2022 - Ramirez Jumbo, Manuel Alejandro (2023)
content of the sports sections on Ecuador's participation in the qualifiers for the Qatar 2022 World Cup. For the analysis, 154 publications of the newspaper El Comercio and 143 publications of the newspaper Extra were identified in the period between October 2020 and March 2022, related to the participation of the national team in the Qatar 2022 qualifiers. The analysis showed that the quality of sports content in the publications of both newspapers showed that the parameters such as clarity, accuracy, brevity, action verbs, reliability, proportion, appropriateness, comprehensibility, and integration registered values above 90% in their publications. However, there are parameters such as relevance and incidence, which drop to 80% and 70%, respectively. In addition, both newspapers report that they disseminate content with ethics and positive communication. Keywords: soccer, journalism, sports, Ecuador, press